Attached or Entrenched? Community Attachment and Place Construction in Southwest Houston, an American Banlieue. Issue 3 (4th May 2017) - Bryerton, Will
ABSTRACT: Community attachment and the cultural contexts of poor urban neighborhoods are both subjects of long traditions of scholarship. Few studies, however, have extended these traditions into increasingly marginalized areas located beyond historically poor ghetto or barrio communities. This article is addressed to the sentiments of attachment and constructions of place among low-income young men in suburban-styled, post–World War II communities on the outer fringes of Houston. Drawing from ethnographic fieldwork, I show that although the young men are widely appreciative of the area's diversity and uniqueness relative to other low-income communities, their brief and superficial exposures to heterogeneity impel them to construct place and express attachments around a complex set of geographic, class, and ethnoracial distinctions. Sensing that such negotiations of the socio-spatial environment might be perceived as fickle, ill informed, and destructive, I discuss implications in relation to cultural heterogeneity and broader concerns about evolving metropolitan poverty contexts.